Implementasi Ketentuan Permohonan Ijin Penempatan Pedagang Kaki Lima Di Jalan Slamet Riyadi Surakarta Tahun 2015 (Tinjauan Yuridis Peraturan Daerah Kota Surakarta Nomor 3 Tahun 2008tentang Pengelolaan Pedagang Kaki Lima) - SULISTINA, Andita; , Dra. Sri Gunarsi, S.H, M.H (2015)
The aim of research to describe the process of licensing vendors in City Walk Jalan Slamet Riyadi Surakarta in 2015 based on the juridical regulations Surakarta area number 3 of 2008 on the management of street vendors following constraints and solutions. This research method is a single case study because the researchers conducted in-depth research and focus attention on the case . Data collection techniques used in this research is by observation, interviews , and review of documents or records. The results showed that : 1 ) Rule number 3 Surakarta area 2008 includes pkl permitting process . Licensing pkl may include ownership pkl permission . permit application by pkl , licensing requirements , the validity period of the permit, and the cost of licensing . 2 ) Constraints in the licensing process at City Walk street vendors Slamet Riyadi Surakarta is a lack of understanding of the pkl of existing regulations so that the requirements are difficult to meet . 3 ) The solution to face obstacles in licensing pkl at City Walk is the Government by way of disseminating the pkl and supervise so that there are no new pkl sell at City Walk Slamet Riyadi street . Keywords : Licensing , street vendors , Regulation No.3th 2008